Screening for Pfhrp2/3-Deleted Plasmodium falciparum, Non-falciparum, and Low-Density Malaria Infections by a Multiplex Antigen Assay. (7th September 2018) - Plucinski, Mateusz M; Herman, Camelia; Jones, Sophie; Dimbu, Rafael; Fortes, Filomeno; Ljolje, Dragan; Lucchi, Naomi; Murphy, Sean C; Smith, Nahum T; Cruz, Kurtis R; Seilie, Annette M; Halsey, Eric S; et al.
Abstract: Background: Detection of Plasmodium antigens provides evidence of malaria infection status and is the basis for most malaria diagnosis. Methods: We developed a sensitive bead-based multiplex assay for laboratory use, which simultaneously detects pan- Plasmodium aldolase (pAldo), pan- Plasmodium lactate dehydrogenase (pLDH), and P. falciparum histidine-rich protein 2 (PfHRP2) antigens. The assay was validated against purified recombinant antigens, monospecies malaria infections, and noninfected blood samples. To test against samples collected in an endemic setting, Angolan outpatient samples (n = 1267) were assayed. Results: Of 466 Angolan samples positive for at least 1 antigen, the most common antigen profiles were PfHRP2+/pAldo+/pLDH+ (167, 36%), PfHRP2+/pAldo−/pLDH− (163, 35%), and PfHRP2+/pAldo+/pLDH− (129, 28%). Antigen profile was predictive of polymerase chain reaction (PCR) positivity and parasite density. Eight Angolan samples (1.7%) had no or very low PfHRP2 but were positive for 1 or both of the other antigens. PCR analysis confirmed 3 (0.6%) were P. ovale infections and 2 (0.4%) represented P. falciparum parasites lacking Pfhrp2 and/or Pfhrp3. Conclusions: These are the first reports of Pfhrp2/3 deletion mutants in Angola. High-throughput multiplex antigen detection can inexpensively screen for low-density P. falciparum, non- falciparum, and Pfhrp2/3 -deleted parasites to provide population-level antigen estimates and identify specimens requiring further molecular characterization. Abstract : A multiplex malaria antigen detection assay was developed to measure pan- Plasmodium antigens aldolase and LDH, and P. falciparum HRP2. Multiplex antigen detection allowed for prediction of malaria infection status, species of infection, and detection of Pfhrp2/3 -deleted parasites.